VARIABILIDADE ALOZIMÁTICA DE Drosophila maculifrons (DIPTERA: DROSOPHILIDAE) DE FRAGMENTOS DE MATA ATLÂNTICA DO SUL E SUDESTE DO BRASIL - Tractz, Carine Costa (2015)
Drosophila maculifrons is a neotropical species that belongs to the guaramunu group and can be found in several Brazilian states, in different phytophisiognomies of the Atlantic forest biome. Atlantic Forest is a priority area for conservation because of its high biodiversity, however it is endangered mostly due to deforestation. Habitat fragmentation can result in reduced biological diversity and decrease in population size due to loss of genetic variability. Moreover, it contributes to process of population isolation and consequent restriction of gene flow, resulting in increased genetic differences between them and the decrease in intrapopulational variability. Thus, this study aimed to assess the allozymatic genetic variability of D. maculifrons populations from south and southeast of Brazil in order to determine the level of genetic diversity and population structure for this species in fragments of Atlantic Forest. In this study, specimens were collected in Canguçu-RS (CAN), Chapecó-SC (CHA), Matão-SP (MAT), Sertãozinho-SP (SER), Cajuru-SP (CAJ). Also, previous data of allozyme variability of D. maculifrons from two conservation areas located in the municipality of Guarapuava-PR (PMA and SSF) were used. The samples were individually submitted to 14% Penetrose 30TM gel electrophoresis in two electrophoretic systems, TC1 and TC2. Data analyses resulted in nine loci: Hk, Pgm, Est, Idh, Gpdh, Me, Mdh-1, Mdh-2 and Mdh-3. Among these, five (55.56%) were polymorphic and the allele frequencies of most these polymorphic (four) were out of the expected by Hardy-Weinberg equilibrium in more than one population, with Pgm locus being the only exception. The average number of alleles per locus was 3.44, ranging from 1 allele for Hk, Gpdh, Mdh-1 and Mdh-3, and 10 alleles for Est. In general, this species showed higher genetic diversity than non-cactophilic species (Ho = 0.2289), and a moderate and statisticaly diferent from zero interpopulational genetic differentiation (Fst = 0.0613), with the confidence interval also including values of low differentiation (<0.05). The genetic distance values, the absence of correlation between these and geographic positioning, besides the high number of migrants (Nm) and effective populational size estimates corroborated the low genetic differentiation among the analyzed populations. A negative and statistically significant correlation between Nm and geographic distance from north to south of the distribution of the populations was observed, suggesting gene flow restricted by distance. Thus, the identity among D. maculifrons populations could be the result of recent and/or historical gene flow. Recent gene flow could be occurring by the presence of corridors connecting forest areas. Similarity among populations could also have been maintained after historical gene flow, with the action of stabilizing selection on the allozymatic loci; or, there was not enough time for the occurrence of higher differentiation among populations since the time when they were not that apart from each other, until the most recent fragmented distribution.